Tinjauan Hukum Ekonomi terhadap Perlindungan Konsumen dalam Transaksi Online - Taufiek, Hikmal Khalis; Ulhaq, Dias Dhiya; Ramadhan, Takbir; Ilham, Muhammad; Rahmadini, Laura; Siswajanthy, Farahdinny (Indonesian Journal Publisher, 2023)
Online transactions are a form of information technology development that provides convenience and benefits for businesses and consumers. However, online transactions also raise various legal issues, especially related to consumer protection. This research aims to examine the economic law review of consumer protection in online transactions in Indonesia. The research method used is descriptive analytical method with normative juridical approach. The data used is secondary data obtained from various sources of information on the internet, such as laws, regulations, journals, articles, and reports. The results show that consumer protection in online transactions in Indonesia is still not optimal, because there are still legal gaps, discrepancies between law and reality, and low legal awareness and responsibility of business actors and consumers. This research recommends the need to improve the quality and quantity of regulations, effective law enforcement, as well as education and advocacy for businesses and consumers in online transactions.